IMPLEMENTASI KEBIJAKAN PROGRAM SOSIAL OLEH LEMBAGA KONSULTASI KESEJAHTERAAN KELUARGA (LK3) DALAM MENANGANI KASUS KEKERASAN DALAM RUMAH TANGGA DI LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Dila Antari; Karjuni Dt Ma'ani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research explains how the implementation of social program policies by the Family Welfare Consultation Institute (LK3) in handling domestic violence cases in Lubuk Alung, Padang Pariaman Regency, is that the Social Service has carried out socialization and counseling to the people of Padang Pariaman Regency, especially in Lubuk Alung, by visiting the district for inform about the LK3 Social Program in dealing with domestic violence. This socialization was also attended by the Head of Sub-district, Kapolsek, Wali Nagari, Wali Korong and other village officials. The objectives of this study are (1) to describe the implementation of social programs by LK3 in handling domestic violence cases in Lubuk Alung, Padang Pariaman Regency. (2) Identifying factors that influence the implementation of social programs by LK3 in handling cases of domestic violence in Lubuk Alung,PadangPariamanRegency. This research uses qualitative methods that are descriptive. The research location was conducted in Lubuk Alung, Padang Pariaman Regency. The data in this study were obtained from interviews, observation and documentation study. The research informants were the Head of Social Empowerment and Handling of the Poor, the Chairperson of LK3 Lubuk Alung in Padang Pariaman Regency, Wali Nagari, Wali Korong, Ninik Mamak, and the Lubuk Alung Community, Padang Pariaman Regency.Based on the results of research conducted at the P3A Social Service, Padang Pariaman Regency and the Family Welfare Consultation Institute (LK3) in Lubuk Alung, it can be concluded that: First, the Implementation of Social Programs by LK3 in handling cases of domestic violence in Lubuk Alung, Padang Pariaman District, P3A Social Service has implemented accordingly with the operational stages of policy implementation, namely there are 3 assessments, (1) interpretation, (2) organization, (3) Implication / application to the community in order to achieve an objective of the LK3 social program in dealing with domestic violence cases in Lubuk Alung, Padang Pariaman Regency. Second, the factors that influence the implementation of social programs by LK3 in handling domestic violence cases in Lubuk Alung, Padang Pariaman Regency consist of four factors that influence the implementation of the LK3 social program in handling cases of domestic violence in Lubuk Alung, Padang Pariaman Regency, namely communication, resources. , disposition, and bureaucratic structure.